Optimalisasi Administrasi Personalia untuk Meningkatkan Kualitas Lembaga Pendidikan Islam - Azka As Sajidah; Ahmad Zainuri; Salsa Anindya (GURUKU : Jurnal Pendidikan dan Sosial Humaniora, 2025)
The development of digital technology and artificial intelligence (AI) has brought significant transformations in various aspects of life, including the character formation of Generation Z. This research aims to explore the role of AI as a "Digital Love Language" in supporting character education in the digital era. The method used is a literature study with a qualitative approach, which examines the literature related to the potential, challenges, and ethical implications of the use of AI in character education. The results of the study show that AI has the ability to provide personalized, adaptive, and contextual learning, so that it can strengthen character values such as empathy, responsibility, and integrity. However, the use of AI also poses risks such as data privacy breaches, technological dependencies, and algorithmic bias. Therefore, synergy is needed between families, communities, and educational institutions in directing the use of AI wisely and ethically. This research emphasizes the importance of digital literacy as a foundation for understanding and managing technology critically, as well as the need for clear ethical regulations in the development and application of AI. With a holistic and collaborative approach, AI can be a strategic instrument in shaping the character of Generation Z who are resilient, ethical, and ready to face future challenges.